PENGARUH PENETAPAN HARGA, KUALITAS PRODUK, KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. GOLDEN TEKNIK SIDOARJO - Adhietia Dharmawan Mattekawang; Ony Kurniawati (STIE Mahardhika, 2023)
In this period era, it is undeniable that the change of technology, be it the world of industry, contractors, or data or information that is developing and is running so fast, that it gets an increasingly fierce business competition. It is not easy for an agency or company to survive in the long term during the ongoing Covid-19 pandemic. In the midst of today's competitive conditions, company management needs to know things to prioritize when managing their company. The purpose of this study is to understand the value of pricing, product quality, and service quality on customer satisfaction either separately or together. It can be seen from the results of this study that pricing has a significant impact of 0.040, product quality 0.015 and service quality 0.000. Overall, it significantly affects customer satisfaction with a value of 0.000.